KOMUNIKASI ANTARPRIBADI GURU DAN MURID PENYANDANG AUTISME - Fajri Agustin; Hamdani M Syam (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2017)
The title of this research is Interpersonal Communication of Teachers and Autism (Study at Sekolah Dasar Luar Biasa Negeri SDLBN Kabupaten Bireuen). The aims of this study is to find out how the interpersonal communication of teachers and autism students and its characteristics along with the steps in achieving effective communication, as well as to find out the supporting factor and the obstacle factor at SDLBN Bireuen. Descriptive qualitative method is used in this study as the approach. Research subject is 5 teachers as the informants. Data collection technique which is used in this study is interview, observation and documentation study. Self Disclosure Theory is used in this study. The results showed the interpersonal communication of teachers and autism look from the characteristics of openness, empathy, support, positive feelings, and similarities to make effective communication. In addition, game equipment becomes a supporting factor in interpersonal communication, although it has little obstacle when hyperactive of autism students relapse, but overall interpersonal communication that is done by teachers and autism students at SDLBN Bireuen works and succeeds.Keyword: